So you want to factor
w^4 = 17w^2 - 16
First, move everything over to the left hand side.
w^4 - 17w^2 + 16 = 0
Now, factor. This is a quadratic in disguise; you just may not realize it yet.
(w^2 - 16)(w^2 - 1) = 0
Both of these are difference of squares, so you have to factor them as well. Note that a^2 - b^2, a difference of squares, factors into (a - b) (a + b).
(w - 4)(w + 4) (w - 1)(w+1) = 0
Therefore, w = 4, -4, 1, -1
To solve the inequality x^2 - 5x > 6, first, do the following.
Move 6 to the left hand side.
x^2 - 5x - 6 > 0
Now, factor the left hand side.
(x - 6) (x + 1) > 0
This means that x = 6 and x = -1 are critical points. What you have to do at this point is to test the behaviour AROUND those points.
You want to test three intervals: (-infinity, -1), (-1, 6), and (6, infinity).
Test a point in the first interval: -100. Do you get a true or false result, when plugging it into (x - 6) (x + 1) > 0? The answer is true, because you get a negative times a negative, which is a positive, and positive numbers are greater than 0. Therefore, we include that interval.
Test a point in the second interval: 0. Plug in 0 for (x - 6) (x + 1) > 0 and we get (-6)(1), which is a negative number. Therefore, we exclude that interval.
Test a point in the third interval: 100. We get a positive number, so we include that interval.
Therefore, our results showed that
(-infinity, -1) passed our test.
(-1, 6) failed our test.
(6, infinity) passed our test
So x = (-infinity, -1) U (6, infinity)
2006-12-07 19:26:21
·
answer #1
·
answered by Puggy 7
·
0⤊
0⤋
Rearrange to form
w^4 - 17w^2 - 16 = 0 let z = w^2
z^2 - 17z - 16 = 0
(z-1)(z-16) = 0 put back z = w^2
(w^2 - 1)(w^2 - 16) Each of these is a difference of squares that factor into the form (a+b)(a-b) = a^2 - b^2. The factors are then
(w+1)(w-1)(w+4)(w-4)
For the second, put all terms on the left
x^2 - 5x - 6 > 0
This factors to (x + 1)(x - 6) > 0
For the product of two terms > 0, both terms are > 0 or both terms are < 0; Both terms are > 0 only if x > 6; both are < 0 only if x < -1
2006-12-08 03:24:47
·
answer #2
·
answered by gp4rts 7
·
2⤊
0⤋
1} w^4=17w^2-16
=w^4+w^2=17-16
=w^6=1
=w^6
2} x^2-5x>6
x^2-5x>6
5x-x^2=6
4x^2=6
4x^=6-2
4x^=4
x^=4/4
x^=1
2006-12-08 03:54:05
·
answer #3
·
answered by mimmy 1
·
0⤊
0⤋
w^4 - 17w² + 16 = 0
(w² -1) (w² - 16) = 0
(w -1) (w + 1) (w + 4) (w - 4) = 0
2006-12-08 03:26:12
·
answer #4
·
answered by starstrucktv 2
·
0⤊
0⤋